Responsible AI in Africa Challenges and Opportunities - Eke, Damian Okaibedi; Wakunuma, Kutoma; Akintoye, Simisola (Social and Cultural Studies of Robots and AI,, 2023)
This open access book contributes to the discourse of Responsible Artificial Intelligence (AI) from an African perspective. It is a unique collection that brings together prominent AI scholars to discuss AI ethics from theoretical and practical African perspectives and makes a case for African values, interests, expectations and principles to underpin the design, development and deployment (DDD) of AI in Africa. The book is a first in that it pays attention to the socio-cultural contexts of Responsible AI that is sensitive to African cultures and societies. It makes an important contribution to the global AI ethics discourse that often neglects AI narratives from Africa despite growing evidence of DDD in many domains. Nine original contributions provide useful insights to advance the understanding and implementation of Responsible AI in Africa, including discussions on epistemic injustice of global AI ethics, opportunities and challenges, an examination of AI co-bots and chatbots in anAfrican work space, gender and AI, a consideration of African philosophies such as Ubuntu in the application of AI, African AI policy, and a look towards a future of Responsible AI in Africa. Damian Okaibedi Eke is Research Fellow at the Centre for Computing and Social Responsibility (CCSR) at De Montfort University, UK. Dr Eke is the Data Governance coordinator for the EU Human Brain Project. His research interests cover critical philosophical issues at the intersection of Technology, Data and Society including; Data Governance, Ethics of Emerging Technologies, Responsible Innovation and ICT4D. Dr. Kutoma Wakunuma is Associate Professor in Information Systems at De Montfort University within the Centre for Computing and Social Responsibility. Her research interests cover social and ethical implications of current and emerging technologies like Artificial Intelligence in the developed and developing world. She is also European CommissionIndependent Ethics Expert. Dr. Simisola Akintoye is a Senior Lecturer in Law at De Montfort University Centre for Law, Justice and Society. She is an International Privacy Practitioner, Data Protection Consultant and the Data Protection Officer for the EU Human Brain Project. Her research involves legal regulation of emerging technologies at national and international levels.